Anchor Fitted with Special Fin for Soil Reinforcement - Abdul Ghani, A.N.; Alias, M.F.Z. (EDP Sciences, 2014)
In order to ensure that anchored soil retention systems are more stable and free from failure, suitable anchors are required. A new technique using anchors with fins were investigated, particularly for mechanically stabilized earth. An experimental laboratory investigation on the behaviour of anchors with fins by using various shapes, sizes, arrangements and lengths were presented. The main purpose of this study is to investigate the load-displacement relationship of pullout anchors with fins embedded in sand. A rectangular model tank with dimensions 0.6 m length, 0.5 m width and 0.3 m high was designed. Models of 15 types of anchors of different lengths (0.3 m, 0.4 m and 0.5 m) with fins using different and various types of lengths, sizes and arrangements embedded in sand, were experimented with . The testing program included 45 tests embedded in dry sand. The experiment was conducted in a soil laboratory at a scale of 1:10. The fin was placed at the end of the anchor shaft that abuts the failing structure which prevents further movement. It was concluded that the size, shape and angle of the fin influenced the pullout capacity of the anchor. Finally, selected anchors were recommended based on their superior performance.